THE EFFECT OF FIRM CHARACTERISTICS AND COLLABORATION EXPERIENCE ON THE RELATIONSHIP BETWEEN DECISION-MAKERS BEHAVIORAL PREFERENCES AND UNIVERSITY'S INNOVATIONS ADOPTION - Kuntadi, Yahya Agung; Sumarwan, Ujang; Najib, Mukhamad; Jahroh, Siti (Jurnal Aplikasi Manajemen, 2020)
This study aims to determine the effect of moderator variables on the relationship between decision-makers behavioral preferences and innovation adoption. Moderator variables are collaboration experience with university and firm characteristics such as ownership of the firm, size of the firm, and status of the firm. There is still a limited understanding of decision-makers behavioral preferences in the adoption of innovations from university, even though this understanding is needed to enhance the success of university and industry collaboration. This study explores several moderator variables that have not been previously studied together before on the relationship between decision-makers behavioral preferences and innovation adoption. This study distributes questionnaires to 365 respondents who are decision-makers of food and beverage firms in Jakarta and surrounding areas. Quantitative analysis of SEM data was carried out with LISREL. The results showed that decision-makers behavior preferences have a significant relationship with innovations adoption and only the status of the firm and collaboration experience with university influence the relationship between decision-makers behavioral preferences and innovations adoption. The results of this study reflect that some moderator variables have a significant effect on the relationship between decision-makers behavioral preferences and innovations adoption. Future research may employ other moderator variables such as government regulations to find out its influence on the adoption of innovation from the university.